Challenges and opportunities in understanding dementia and delirium in the acute hospital - Jackson, Thomas A.; Gladman, John R.F.; Harwood, Rowan H.; MacLullich, Alasdair M.J.; Sampson, Elizabeth L.; Sheehan, Bart; Davis, Daniel H.J. (Public Library of Science, 2017)
What is the problem?